Civilisation and Human Niche Construction. Issue 1 (14th December 2017) - Arroyo-Kalin, Manuel; Wengrow, David; Fuller, Dorian Q.; Stevens, Chris J.; Wollstonecroft, Michèle
Abstract : This short paper introduces the special section of three articles under the general heading of 'Civilisation and the Construction of the Human Niche', organised by the 'Domestication, Niche Construction and the Anthropocene' research network at the UCL Institute of Archaeology.